PENGARUH BEBAN KERJA DAN STANDAR OPERASIONAL PROSEDUR TERHADAP KINERJA KARYAWAN PT DWI MULTI MAKMUR JAKARTA - Apriana, Apriana; Nurhayaty, Ety (LP2M Universitas Bina Bangsa, 2024)
Human resources have an important role in moving and advancing an organization or company. Every company always strives to encourage employees to be able to provide an achievement and meet the targets set by the company. With the achievement and fulfillment of targets, of course, it must be accompanied by supporting factors that can improve employee performance such as appropriate workloads and standardized operational procedures. For this reason, the company must maintain a balance between the two to produce optimal performance for PT Dwi Multi Makmur employees. The population of this study is all employees of PT Dwi Multi Makmur totaling 31 respondents, all of which are used as samples because they use total sampling. The analysis method in this study uses multiple linear analysis. The test tool uses SPSS version 26. The results showed that the workload variable had a significant effect on employee performance with a value of 0.039 < 0.05, while the standard operating procedure variable had a significant effect on employee performance with a significance value of 0.00 < 0.05. In the simultaneous test, workload and standard operating procedures had a positive effect on the performance of PT Dwi Multi Makmur's employees based on an Fcal value of 43.192